2022
DOI: 10.3389/fpsyg.2022.845769
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Coping Strategies Scale for Use in Chinese Contexts

Abstract: Individuals’ coping strategies have a profound effect on how well they respond to negative life events. Despite this, most coping strategies instruments that are available currently have been developed exclusively in Western contexts. In the present study, a Coping Strategies Scale (CSS) for use with Chinese participants was developed and validated based on responses from 734 Chinese university students (334 male, 399 female, 1 other). Results supported a seven-factor structure for the CSS, which included the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 71 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…The Chinese version of the CSS [ 58 ] was used to measure the coping strategies participants chose to adopt in the COVID-19 context. The CSS includes 30 specific strategies which can be categorized into seven general types of coping strategies: Withdrawal, Positive Adaptation, Problem-solving, Disengagement, Prosocial Focus, Seeking Emotional Support, and Self-regulation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Chinese version of the CSS [ 58 ] was used to measure the coping strategies participants chose to adopt in the COVID-19 context. The CSS includes 30 specific strategies which can be categorized into seven general types of coping strategies: Withdrawal, Positive Adaptation, Problem-solving, Disengagement, Prosocial Focus, Seeking Emotional Support, and Self-regulation.…”
Section: Methodsmentioning
confidence: 99%
“…Respondents were asked to rate how frequently they used each of the strategies using a five-point scale (Never = 1, Rarely = 2, Sometimes = 3, Often = 4, Always = 5). Zhao et al [ 58 ] have found that this instrument has sound internal structure and reliability in Chinese university populations.…”
Section: Methodsmentioning
confidence: 99%
“…The score can indicate the primary coping mechanism of the individual (e.g., problem-focused, emotion-focused, avoidant). Low scores on all subscales may indicate that the responder does not experience many stressors with which he needs to cope, lacks reflective ability or has poor coping mechanisms [13].…”
Section: Coping Behavior Questionnaire (Cope)mentioning
confidence: 99%